Association of Understanding the Concept of Khalifah Fil Ard on Ecological Responsibility of Primary School Students - Dhiya Roiha Anah; Nurhawatee Sulongsen; Ellen Prima (Institut Agama Islam Negeri Palopo, 2026)
This study investigated the relationship between students' ecological responsibility and their comprehension of the concept of khalifah fil ard at MI Darun Najah Gandatapa, Banyumas Regency, Indonesia. The study used a correlational design and a quantitative methodology. Twenty-five Grade V students, selected through total sampling, served as participants. A questionnaire measuring students' comprehension of the concepts of khalifah fil ard and ecological responsibility was used to gather data. Expert judgment and item-total correlation analysis were used to validate the instrument, which showed high reliability (Cronbach's Alpha = 0.954). IBM SPSS Statistics Version 27 was used to analyze the data using descriptive statistics, linearity and normality tests, and simple linear regression. The findings showed a significant correlation between students' ecological responsibility and their comprehension of the concept of khalifah fil ard (β = 0.997, t = 45.140, p < 0.05). A significant amount of the variance in ecological responsibility was statistically linked to students' comprehension of the concept of khalifah fil ard, according to the coefficient of determination, which displayed an R2 value of 0.993. These results imply that students tend to exhibit greater ecological responsibility when they have a greater awareness of their role as Allah's stewards on earth. The study backs up Islamic environmental ethics' theoretical stance, which places a strong emphasis on human responsibility for environmental stewardship. However, because the study only included a small sample from one madrasah, the results should be interpreted with caution. It is advised that larger and more varied sample sizes be used in future research to better investigate the variables linked to students' ecological responsibility.